A Survey of the Microbiological Quality of Commercial Frozen Prawn Products - Pillai, V K; Lekshmy, A; Govindan, T K; Mathen, Cyriac; Iyer, H Krishna (Fishery Technology, 1965)
A Survey of the Microbiological Quality of Commercial Frozen Prawn Products